Hoarding Wealth in the Perspective of the Qur’an: A Semantic Study of the Word Kanz - Ihya Rizky Audia; Zubair Zubair; Ali Hasan Al Bahar; M. Husni T; Baso Pallawagau (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to examine the semantic relations of the word kanz based on the Qur’anic foundation of meaning, with data obtained through a literature review primarily from the verses of the Qur’an, and secondarily from hadith, works of tafsīr and fiqh, as well as other relevant sources analyzed using semantic field theory. The findings show that the word kanz and its derivations appear in seven verses of the Qur’an, conveying the concept that wealth which is accumulated and stored is a blessing and trust (amānah) from Allah, thus bound by divine regulations. Its usage varies depending on context: negatively (QS. 10:34–35; QS. 28:76; QS. 26:58) when detached from its role as a blessing and trust, leading to harmful consequences, and positively (QS. 18:82) when directed toward noble purposes such as supporting orphans. In other instances (QS. 25:8; QS. 11:12), kanz appears within the mockery of disbelievers toward the Prophet Muhammad (peace be upon him), demanding material treasures as proof of prophethood. Therefore, the Qur’anic concept of kanz does not merely denote the storage of wealth but emphasizes its nature as a trust that requires responsible stewardship, where proper management leads to prosperity, while hoarding driven by greed results in destruction.